Pendekatan Client Centered Teraphy - Erna Hasni (Proceedings of Annual Conference on Islamic Educational Management, 2021)
All the problems of human life, whether phsycal, psychological,, family, social, or religious, demand a solutation. An education counselor is one of the determinants of education direction and aids students problem solving. The success of a learning can not be separated from the role of a counselor, for that reason, so that learning goals in schools in particuler and educational goals in general can be achieved it depends on the quality of the human resource of a counselor. Then in this discussion, counseling is intended as a special service in a direct face-to-face relationship between counselor and client. In this connection the client’s problem is examined and strived for alleviation, as far as possible with the strength of thr fabric itself. In that regard, counseling is consideres as the most important service effort in the implementation of the client problem alleviation function. It is even said that counseling is the “ heart of his heart” a comprehensive guidance service. To be able to master the “heart of heart” guidance, a counselor need to learn, apply, and have extensive experience in counseling service with all the ins and outs ( Prayetno,Erman,2013:289). Counseling services are organized officially Problem boundaries throught counseling Stages of the effectiveness of alleviating problems throught counseling Counseling approcaches and theories Counseling in a different work environment.